1991
DOI: 10.1254/jjp.57.495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the New Anti-Ulcer Agent KB-5492 on Experimental Gastric Mucosal Lesions and Gastric Mucosal Defensive Factors, as Compared to Those of Teprenone and Cimetidine.

Abstract: ABSTRACT-Effectsof KB-5492, a new anti-ulcer agent, on various experimental gastric mucosal lesions and mucosal defensive factors in rats were compared with those of teprenone and cimetidine. KB-5492 administered orally at 12.5 200 mg/kg inhibited water-immersion stress and indomethacin-induced gastric mucosal lesions in a dose-dependent manner with ED50 values of 46 and 27 mg/kg, respectively, indicat ing that KB-5492 was more potent than teprenone but less potent than cimetidine. KB-5492, administered orally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
115
1
7

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 26 publications
2
115
1
7
Order By: Relevance
“…Lansoprazole, substance orally used as a positive control in this experiment, at a dose of 30 mg.kg -1 , provided 68% protection against the gastric lesions induced by ethanol. These results indicated a promising antiulcerogenic activity of the MeOH extract and suggested that an antisecretory or cytoprotective action may be involved (Morimoto et al 1991).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Lansoprazole, substance orally used as a positive control in this experiment, at a dose of 30 mg.kg -1 , provided 68% protection against the gastric lesions induced by ethanol. These results indicated a promising antiulcerogenic activity of the MeOH extract and suggested that an antisecretory or cytoprotective action may be involved (Morimoto et al 1991).…”
Section: Resultsmentioning
confidence: 82%
“…These experiments were done as described by Morimoto et al (1991) Rats were fasted for 24 h and MeOH extract, lansoprazole (30 mg.kg -1 ) or vehicle (solution 0.9% NaCl) was administered orally. One hour after treatment, the animals received an oral dose of one ml of absolute ethanol and were sacrificed one hour later, as described before.…”
Section: Gastric Mucosal Lesions Induced By Absolute Ethanolmentioning
confidence: 99%
“…To confirm the results that demonstrated the gastric protective effect of the EB1 and EB3 samples against the ethanol model, the indomethacin model (a medicine that produces ulcers in laboratory animals) was carried out (Morimoto et al, 1991;Borrelli & Izzo, 2000). Regarding the application of the referred experimental model, it was verified that the sample of the latex exhibited high antiulcerogenic activity, impeding the formation of ulcerative lesions in the stomach of the rats treated with this material (Figure 3).…”
Section: Controlmentioning
confidence: 73%
“…Although KB-5492 at anti-ulcer doses did not affect either basal or histamine-stimulated gastric acid secretion in rats (3,4), it increased the gastric mucosal blood flow (4) and prevented the reduction of hexosamine content induced by aspirin in rat gatric mu cosa (4). These findings strongly suggest that KB-5492 en hances gastric mucosal defensive factors.…”
mentioning
confidence: 85%
“…KB-5492, 4-methoxyphenyl 4-(3,4,5-trimethoxybenz yl)-1-piperazineacetate monofumarate monohydrate, is a new anti-ulcer agent previously shown to prevent various experimental gastric mucosal lesions in rats including those induced by oral administration of aspirin or acidified aspirin (3,4). Although KB-5492 at anti-ulcer doses did not affect either basal or histamine-stimulated gastric acid secretion in rats (3,4), it increased the gastric mucosal blood flow (4) and prevented the reduction of hexosamine content induced by aspirin in rat gatric mu cosa (4).…”
mentioning
confidence: 99%